1982
DOI: 10.1159/000260626
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Radiographical Diagnosis in 8-Year-Old Schoolchildren with Low Caries Activity

Abstract: In caries prevalence studies it is common practice to use bite-wing radiographs for the diagnosis of approximal caries. In many populations there is a tendency for caries levels in children to decrease over the last 10–15 years. The aim of the present study was to investigate the necessity of routine bite-wing radiographs in a low caries population. A clinical and radiographical dental examination was carried out in a group of 174 Dutch schoolchildren in 1979, using Marthaler’s reduced-count method. Clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 3 publications
2
9
0
Order By: Relevance
“…On the other hand, other authors have reported that the use of bitewing radiography did not result in a significant increase in permanent dentition caries experience rates in subjects under the age 12 years. [19][20][21] As the majority of permanent teeth in children under 12 years have been erupted for relatively short periods of time and their proximal caries experience was low, inclusion of bitewing radiography for epidemiological purposes for this age group of children would yield only a minimal increase in caries rates over the visual examination. 9,10,22 Previous studies suggest that bitewing radiography has the greatest value in detecting caries in subjects with the highest susceptibility to caries.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other authors have reported that the use of bitewing radiography did not result in a significant increase in permanent dentition caries experience rates in subjects under the age 12 years. [19][20][21] As the majority of permanent teeth in children under 12 years have been erupted for relatively short periods of time and their proximal caries experience was low, inclusion of bitewing radiography for epidemiological purposes for this age group of children would yield only a minimal increase in caries rates over the visual examination. 9,10,22 Previous studies suggest that bitewing radiography has the greatest value in detecting caries in subjects with the highest susceptibility to caries.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these considerations the data of children aged 8 through 12 [Ruiken et al, 1982[Ruiken et al, , 1986 and the new 14-year data were reassessed using a different method of analysis, i.e. calculation of sensitivity and negative predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…It was expected that with higher incidence of approximal lesions in la ter life omission of a radiographic examination would result in a substantial loss of information [Ruiken et al, 1982]. The aim of the present study is to evaluate the usefulness of caries diagnosis with the aid of bitewing radiographs in an age-group older than 12 years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the general decline in dental caries prevalence and incidence in most Western countries has been accompanied by a change in lesion behaviour [Pitts, 1993] and some workers have questioned the necessity of bitewing radiographs in populations with low caries experience or in age groups with newly erupted teeth. For example, earlier studies in child populations with low caries prevalence showed that approximal dentinal lesions were an infrequent phenomenon in children under the age of 12, and so bitewings were said to be of little value to clinical diagnosis [Ruiken et al, 1982[Ruiken et al, , 1986. It is noteworthy that, although these studies were described at the time as having been conducted in low-caries-prevalence populations (a mean DMFS of 5.3 from clinical examination alone, which became 6.0 after 'radiographic correction'), such data would now be typical of a high-caries child population, given current caries patterns [Foster Page et al, 2005].…”
mentioning
confidence: 99%